Countdown Bin Laden the untold story of the 247-day hunt to bring the mastermind of 9/11 to justice - Wallace, Chris 1947-; Weiss, Mitch (Avid Reader Press, an imprint of Simon & Schuster Inc., 2021)
Chronicles the final months of the hunt for Osama bin Laden
Keywords: Ibn-Lādin, Usāma -- 1957-2011; USA -- Central Intelligence Agency; 21st Century history; Terrorism, revolutions, coups; Military history; Bin Laden, Osama / 1957-2011 / Assassination; Special operations (Military science) / United States; Special operations (Military science) / Pakistan; United States / Military policy; HISTORY / United States / 21st Century; HISTORY / Military / United States; POLITICAL SCIENCE / Terrorism; Bin Laden, Osama / 1957-2011; Assassination; Military policy; Special operations (Military science); Pakistan; United States